Numerical Study of Hydrodynamics in the waters of Balikpapan Bay using Finite Volume Method - Rahman, Suci Erniya; Yusuf, Mustaid; Nasution, Yuki Novia (GEOSAINS KUTAI BASIN, 2022)
Suci Erniya Rahman. 2021. Numerical Study Hydrodynamic in the waters of Balikpapan Bay using Finite Volume Method. Supervised by Dr. Sc. Mustaid Yusuf, M.Si. and Yuki Novia Nasution, S.Si., M.Sc. Faculty of Mathematics and Natural Sciences, Mulawarman University. The hydrodynamic model FVCOM (Finite Volume Coastal Ocean Model) using the approach method finite volume has been applied to determine the distribution of tidal current patterns in the Balikpapan Bay area. The simulation was carried out for 30 days using river discharge and tides as generating forces. The simulation results has verified by using the Root Mean Square Error (RMSE) method on observation data in the Balikpapan Bay area. The results of the simulation and observation verification have a good agreement, which is 0.09917 meters. The smaller (closer to zero) RMSE value, is the better results of the observation and simulation match. The results of study showed that the pattern and average current velocity in Balikpapan Bay for 15 days (11-26 October 2012) was dominant out of the bay.